Influence of acoustical properties of a listening room on the consistency between sound fields reproduced using standard stereo technique and headphone technique with HRTF processing - Sawicki, Jerzy; Mickiewicz, Witold (Archives of Acoustics, 2006)
The analysis of acoustical properties of three different listening rooms and its influence on the subjective and objective fidelity and consistency between sound fields reproduced using two loudspeakers in standard stereo configuration and headphone feed with the signal processed using a method of sound externalization developed by the authors based on the modified HRTF (Head Related Transfer Function) technology are presented in the paper. The experiments allow more deep insight into the sound source localization by a human in a closed space and an improvement of the processing algorithm for the sound presentation using headphones.